New geldanamycin derivatives with anti Hsp properties by mutasynthesis. Issue 21 (15th May 2019) - Hermane, Jekaterina; Eichner, Simone; Mancuso, Lena; Schröder, Benjamin; Sasse, Florenz; Zeilinger, Carsten; Kirschning, Andreas
Abstract : Four new non hydroquinone derivatives of geldanamycin are prepared by mutasynthesis and their antiproliferative as well as inhibitory properties for human as well as bacterial heatshock proteins are evaluated. Abstract : Mutasynthetic supplementation of the AHBA blocked mutant strain of S. hygroscopicus, the geldanamycin producer, with 21 aromatic and heteroaromatic amino acids provided new nonquinoid geldanamycin derivatives. Large scale (5 L) fermentation provided four new derivatives in sufficient quantity for full structural characterisation. Among these, the first thiophene derivative of reblastatin showed strong antiproliferative activity towards several human cancer cell lines. Additionally, inhibitory effects on human heat shock protein Hsp90α and bacterial heat shock protein from H. pylori HpHtpG were observed, revealing strong displacement properties for labelled ATP and demonstrating that the ATP-binding site of Hsps is the target site for the new geldanamycin derivatives.